FOREIGN LANGUAGES IN THE TERMS OF EMPLOYMENT OF PERSONS WITH VISUAL IMPAIRMENT - Malinovská, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
A good job is one of the most important criteria of the quality of life of people with severe visual impairment. It not only helps people to widen their range of social interactions, but also to improve people´s skills and abilities. This study focuses on the difficulties these people experience in the study of foreign languages, and whether they perceive the learning of foreign languages as an important part of their work.This qualitative type of research was made through interviews and studying of clients´ documentation. Participants in the study were people of mature age, who have been forced to change their jobs, or even the qualifications because of the acquired disability. Currently, these people use the services of a local specialized Center for people with visual impairments, where the study took place.The survey results show that clients do not only perceive the knowledge of a foreign language as an important component of their quality of life, but also would like to use foreign languages in the workplace. Unfortunately, this is often impossible because of the lack of appropriate materials and training courses, and in some cases, because of low internal motivation of these people.